POWERFUL KNOWLEDGE AS THE FUTURE OF SCHOOL CURRICULUM - Elksne, Gunita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The global, social, economic and technological conditions of the 21st century are drastically changing the way societies and education policymakers understand the goals of education. Pedagogy has always been about how to pass on the knowledge, skills, values, and development of one's personality to the next generation, to create the conditions for growth that meet everyone’s needs and provide equal opportunities. However, today this issue has become more relevant than ever as the world is changing very rapidly, society, its values, and needs are changing, as confirmed by the UNESCO goals for 2030.Young, pointing out that in many countries education policy neglects what knowledge a student needs today, creates a theory of "Powerful knowledge" based on the work of educational sociology authors such as Durkheim, Bernstein, Bourdieu. The goal of this paper is to conduct a literature review of the concept of 'powerful knowledge'.Since the year 2009, this term has been described in many articles but is still in development. Analyzing the works of Young and Muller, as well as getting to know works of other authors who complement and develop the concept (Wheelahan, Lambert, Deng, etc.) and those who are more skeptical (White), the definition and features of Powerful Knowledge have been revealed and scientists' thoughts on what makes knowledge "powerful", why it is needed, what place it can play in school curricula have been collected, as well as highlighting questions that have not yet been answered clearly.